Enhanced energy storage properties of Sr(Sc0.5Nb0.5)O3 modified (Bi0.47La0.03Na0.5)0.94Ba0.06TiO3 lead-free ceramics - Xie, Jinglong; Dai, Zhonghua; Ding, Xiangdong; Fan, Xing; Liu, Weiguo; Zhang, Lin; Li, Jinglei (Journal of materials science, 2020)
Excellent energy storage performance of dielectric capacitors is highly desired in all kinds of energy storage devices. In this study, Sr(Sc 0.5 Nb 0.5 )O 3 was introduced to enhance the energy storage properties of (Bi 0.47 La 0.03 Na 0.5 ) 0.94 Ba 0.06 TiO 3 (BLNBT) ceramics. All ceramic samples were sintered densely, and the phase structure, microstructure, dielectric and ferroelectric properties were then systematically investigated. Two distinct dielectric anomaly peaks, which are detected from the dielectric properties as a function of temperature, suggest not only a phase transition, but also indicate typical relaxor features. The breakdown strength is significantly improved, and the polarization versus electric field hysteresis loops become slim with the increasing content of SSN. The optimum energy storage performance is achieved in 0.85BLNBT–0.15SSN ceramic with the recoverable energy density of 1.83 J/cm 3 and energy efficiency of 82.32% under a moderate electric field of 185 kV/cm. The excellent energy storage performance of 0.85BLNBT–0.15SSN ceramic makes it a promising candidate material for advanced pulsed power capacitors.